Pemetaan Sosial Ekonomi Masyarakat Pematang Siantar (Studi Kasus Masyarakat Siantar Barat) - Ami Dilham; Umar Maya Putra (HUMAN FALAH: Jurnal Studi Ekonomi dan Bisnis Islam, 2016)
This study aimed to analyze the socio-economic mapping with case studies Siantar Siantar District of Western society. The purpose of this study is to see how far the characteristic ability of socioeconomic District of Siantar Barat both in the category of business, inspiration and medium enterprises, business development, years of starting the business, the age of the respondent, number of employees, type of business development assistance, the type of assistance expected private agencies / SOE and suggestions for the development of businesses that are part of the socio-economic mapping Siantar. The data used is primary data using questionnaires to society western range. The results of this study indicate that the Business Name: Herb Healthy Fresh: 33%, Business category: Drinks totaling 82% Address Enterprises: Street Football on: 53%, Inspiration Making Business: 17% was from the beginning migrated to focus on making herbal medicine, Yang assist in the creation of business: wife of 19%, Points of Creation: the direct business 89%, Start of Business: in 1974 as much as 9.1%, Business Start hour: 45% starting at 8:00, Business development: developing .: help Available : Pertamina Depot Siantar as much as 51%. The assistance is expected from the Private Sector, Blender, Pots, Dandang as much as 33%, Advice for Business Development: 73% The existence of business coaching.